Interactions between plants and an opportunistic human pathogen, Pseudomonas aeruginosa - Weir, Tiffany L., author; Schweizer, Herbert P., advisor; Vivanco, Jorge M., advisor (Colorado State University. Libraries, 2008)
Pseudomonas aeruginosa is an opportunistic human pathogen that can be found living in soil, water, or saprophytically on plant tissues. It is important to understand the pathology of this organism under variable conditions because of its ability to survive in diverse environments, its role in human disease, and its use as a model organism in studies on biofilm formation, quorum-sensing, and pathogenicity. To this end, a number of unconventional model systems, including plants, nematodes, and fruit flies, have been developed to study the pathology of P. aeruginosa. In the present study, the interactions between P. aeruginosa and plants, with respect to pathogenicity, quorum-sensing, and microbial ecology are further explored. To examine what factors are important in the pathogenicity of P. aeruginosa in a plant system, compatible and incompatible cultivars of Nicotiana tabacum were infiltrated with the pathogen. Bacterial growth in planta was monitored and P. aeruginosa PAO1 gene expression was examined 24 hours after infiltration into the hosts. The data suggests that, in addition to known virulence factors, the acquisition of micronutrients such as sulfate and inorganic phosphate are also important in disease development. The results of this study also suggest that type III secretion systems may be important in P. aeruginosa's ability to infect plants, and that differences in host response, i.e. salicylic acid signaling, are determining factors in host compatibility. Another aspect of this study was to utilize the natural interactions between plant roots and soil-borne bacteria to identify root exudates that interfere with bacterial quorum sensing (QS), particularly in P. aeruginosa. Quorum sensing in P. aeruginosa controls the expression of several secreted factors that are important in virulence of the pathogen, and preventing infections by inhibition of quorum sensing is a current therapeutic target. Unfortunately, while many of the exudates appeared to have some affect on QS in general, none had strong activity against P. aeruginosa QS systems. However, one class of chemicals, triterpene saponins, was shown to be active in a lux-based QS reporter. Finally, preliminary data suggesting that root exudates can influence competitive outcomes between two soil-borne bacterial species are also presented. The interactions between bacteria are typically studied in nutrient rich medium under defined laboratory conditions. Under these conditions, P. aeruginosa outcompetes Agrobacterium tumefaciens, two bacteria that potentially compete for the same niche in the soil. However, when Arabidopsis thaliana is factored into this equation, growth of A. tumefaciens is favored. Furthermore, the negative effects of P. aeruginosa on the growth of A. thaliana were reduced.
Keywords: microarray; plant model; Pseudomonas aeruginosa; quorum sensing; sulfate; virulence factors; microbiology; plant sciences; plant pathology